2021
DOI: 10.1007/s00148-021-00825-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the skill content of jobs

Abstract: There is significant heterogeneity in actual skill use within occupations even though occupations are differentiated by the task workers should perform during work. Using data on 12 countries which are available both in the Programme for the International Assessment of Adult Competencies survey and International Social Survey Program, we show that women use their cognitive skills less than men even within the same occupation. The gap in skill intensity cannot be explained by differences in worker characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…However, the meaning of certain terms may vary from country to country, as it depends on the cultural, economic and political environment in a given country [3,21]. This is in line with the findings of Hungarian and Danish authors claiming we know much less about what people actually do at their workplaces and the causes of within-occupation gender differences compared to relatively robust literature evidence on general gender differences in the labor market [22,23]. Although the literature agrees on two dimensions of the division of job attributes (external and internal), we are not sure whether these two dimensions are present or understood in the same way in each country.…”
Section: Measurement and Classification Of Job Attributes: A Literatu...supporting
confidence: 56%
“…However, the meaning of certain terms may vary from country to country, as it depends on the cultural, economic and political environment in a given country [3,21]. This is in line with the findings of Hungarian and Danish authors claiming we know much less about what people actually do at their workplaces and the causes of within-occupation gender differences compared to relatively robust literature evidence on general gender differences in the labor market [22,23]. Although the literature agrees on two dimensions of the division of job attributes (external and internal), we are not sure whether these two dimensions are present or understood in the same way in each country.…”
Section: Measurement and Classification Of Job Attributes: A Literatu...supporting
confidence: 56%
“…Participants provided demographic information, including gender, age, education, job and organizational tenure, and position occupied. Considering the importance of these variables for the happy-productive worker thesis (e.g., Harari et al, 2017 ; Petö and Reizer, 2021 ; Previtali and Spedale, 2021 ), we controlled for their potential effects in statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical and horizontal mismatches may contribute to gender inequality in labor income of tertiary education graduates because the probability of experiencing a mismatch is not necessarily the same for men and women (e.g. Addison et al, 2020; Petö and Reizer, 2021).…”
Section: Previous Researchmentioning
confidence: 99%
“…Based on data from the Programme for the International Assessment of Adult Competencies survey (PIAAC), Petö and Reizer (2021) analyzed gender differentials in skill use in 12 countries and found that, even within the same occupation, women report a lower usage of numeracy, literacy, and ICT skills compared to men. At the same time, skills and skill-task matches lead to income premiums even within the same occupation.…”
Section: Previous Researchmentioning
confidence: 99%